HUBUNGAN BERAT TAS SEKOLAH DENGAN GANGGUAN MUSKULOSKELETAL PADA SISWA SD SARASWATI 1 DENPASAR - Widya Artha, I Gede Putu (E-Jurnal Medika Udayana, 2016)
The elementary school is one level of education in Indonesia. The number of subjects in elementary schools cause students should bring a lot of books in their bag. One type of bag that is often used by elementary school students is a backpack. Backpack can carry a lot of stuff but it can cause musculoskeletal disorders. This study aims to determine the relationship of the weight of school bags with musculoskeletal disorders at elementary students Saraswati 1 Denpasar. This study used a cross-sectional study . The sample used was grade 5 in elementary Saraswati 1 Denpasar which amounted to 103 people. Instruments in this study was a questionnaire Nordic Body Map . Data were analyzed with Spearman test to determine the relationship of the weight of school bags with musculoskeletal disorders at elementary students Saraswati 1 Denpasar. The results showed correlated between the heavy bag with musculoskeletal disorders at elementary students Saraswati 1 Denpasar (p = 0.001). The body parts most commonly experienced musculoskeletal disorders is back, shoulder and neck. Results of this study are expected to educate the public about ergonomic heavy bag for elementary school students. Keywords: Musculoskeletal Disorders, Weight Bag, Elementary School